A study on corrosion resistance of Sodium Metavanadate (NaVO3) coated on AZ91D Magnesium alloy by anodizing technique - Nor Fadzilah, Toha (Universiti Malaysia Perlis (UniMAP), 2015)
Master of Science in Manufacturing Engineering